Managing waste exports when closure risks are endogenous - Frank Stähler; Peter Michaelis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
This paper provides a rationale for taxing waste exports when closure risks are endogenous in that they depend on the importing country's accumulated stock of waste. The paper shows that the optimal time path of waste exports requires a progressively increasing tax rate which even surmounts a Hotelling tax which tackles the problem by evaluating the expected closure stock.
Keywords: 330; Sonderabfall; Abfallentsorgung; Außensteuerrecht; Embargo; Theorie